Semantics and Pragmatics of Non-Canonical Word Order in South Asian Languages: of lag- ‘Begin’ as an Attitude-Marker in Hindi-Urdu - Hook, Peter (Lingua Posnaniensis, 2012)
This paper examines possible motivations for departures from canonical clause-final word order observed for the finite verb in Hindi-Urdu and other modern Indo-Aryan languages. Depiction of speaker attitude in Premchand's novel godān and the imperatives of journalistic style in TV newscasts are shown to be prime factors. The emergence of V-2 word-order in Kashmiri and other Himalayan languages may have had a parallel history.